The Baltimore Sun Susan Reimer column - Reimer, Susan (McClatchy - Tribune Business News, 2011)
Pennsylvania's Rick Santorum is a conservative Catholic who tried to have language inserted into the No Child Left Behind legislation that would have required that the religious theory of intelligent design be taught in schools.